Source mechanisms and transport patterns of tropospheric bromine monoxide: findings from long-term multi-axis differential optical absorption spectroscopy measurements at two Antarctic stations - Frieß, Udo; Kreher, Karin; Querel, Richard; Schmithüsen, Holger; Smale, Dan; Weller, Rolf; Platt, Ulrich (Atmospheric chemistry and physics, 2023)
The presence of reactive bromine in polar regions is a widespread phenomenon that plays an important role in the photochemistry of the Arctic and Antarctic lower troposphere, including the destruction of ozone, the disturbance of radical cycles, and the oxidation of gaseous elemental mercury. The chemical mechanisms leading to the heterogeneous release of gaseous bromine compounds from saline surfaces are in principle well understood. There are, however, substantial uncertainties about the contribution of different potential sources to the release of reactive bromine, such as sea ice, brine, aerosols, and the snow surface, as well as about the seasonal and diurnal variation and the vertical distribution of reactive bromine. Here we use continuous long-term measurements of the vertical distribution of bromine monoxide (BrO) and aerosols at the two Antarctic sites Neumayer (NM) and Arrival Heights (AH), covering the periods of 2003–2021 and 2012–2021, respectively, to investigate how chemical and physical parameters affect the abundance of BrO. ...
Gesehen am 29.11.2023